Spatial variability of marine bacterial and archaeal communities along the particulate matter continuum. Issue 24 (24th November 2017) - Mestre, Mireia; Ferrera, Isabel; Borrull, Encarna; Ortega‐Retuerta, Eva; Mbedi, Susan; Grossart, Hans‐Peter; Gasol, Josep M.; Sala, M. Montserrat
Abstract: Biotic and abiotic particles shape the microspatial architecture that defines the microbial aquatic habitat, being particles highly variable in size and quality along oceanic horizontal and vertical gradients. We analysed the prokaryotic (bacterial and archaeal) diversity and community composition present in six distinct particle size classes ranging from the pico‐ to the microscale (0.2 to 200 μm). Further, we studied their variations along oceanographic horizontal (from the coast to open oceanic waters) and vertical (from the ocean surface into the meso‐ and bathypelagic ocean) gradients. In general, prokaryotic community composition was more variable with depth than in the transition from the coast to the open ocean. Comparing the six size‐fractions, distinct prokaryotic communities were detected in each size‐fraction, and whereas bacteria were more diverse in the larger size‐fractions, archaea were more diverse in the smaller size‐fractions. Comparison of prokaryotic community composition among particle size‐fractions showed that most, but not all, taxonomic groups have a preference for a certain size‐fraction sustained with depth. Species sorting, or the presence of diverse ecotypes with distinct size‐fraction preferences, may explain why this trend is not conserved in all taxa.